World tables, 1976 : from the data files of the World Bank - World Bank.; International Bank for Reconstruction and Development (Baltimore : Published for the World Bank [by] Johns Hopkins University Press, 1976)
This book is about data that are published on world tables.
Includes bibliographical references and index.
oo 08/04/2019
Loans
Keywords: Economic history; Social history; Statistics; Economic indicators; Social indicators